Marginal zone lymphoma of arytenoid cartilage: a rare malignancy of the larynx - Bernaciak, Julia; Nogal, Piotr; Iwanik, Katarzyna; Jackowska, Joanna (Contemporary Oncology/Współczesna Onkologia, 2026)
Marginal zone lymphomas (MZL) are indolent non-Hodgkin lymphomas (NHL), which develop from B lymphocytes present in secondary lymphoid organs. They are the second most popular kind of NHL, constituting 7% of all cases [1, 2]. Marginal zone lymphomas can be divided into three subtypes: nodal, splenic and extranodal mucosa-associated lymphoid tissue lymphoma. The third type is the most common (60.8% of cases) [3]. The most frequent sites of its location are: stomach (30%), adnexa, salivary gland, lung, skin, thyroid and breast [1]. Therefore, presence of MZL in arytenoid cartilage, which is reported below, is a very infrequent event. Extranodal marginal zone lymphoma (EMZL), which has an indolent course, rarely occurs in arytenoid cartilage. Diagnosis of the condition in such an infrequent location is challenging and demands the use of various methods, such as magnetic resonance imaging and histopathological examination of the tissue sections acquired during microlaryngoscopy. We present an infrequent case of a 61-year-old patient who was diagnosed with EMZL of arytenoid cartilage after a four-year period of surveillance and examinations. Chemoimmunotherapy was implemented in this case as a successful method of treatment, as it included bendamustine and rituximab. The disease was in remission after the treatment.